Entre prezas e rolês: pixadores e pixações de / em Belo Horizonte - Rodrigo Amaro de Carvalho (2013)
This research sought to present an ethnography of the pixadores in/the city of Belo Horizonte, aiming, in general, to investigate and understand their modes socialities, their representations and uses of the city, and therefore the territorialities created by these agents from their paths and interventions through the cityscape. We approached along the way search pixadores dominate an entire set of knowledge around the practice of graffiti, which allowed us to show a correspondence between: styles, materials, techniques and supports. Discuss this issue was very important to think about how, throughout history, were maintained socialities between these groups, as well as to consider the exchange with the style of São Paulo and Rio de Janeiro. Thus, more emphatic, we defend the thesis that, despite the intense exchanges stylistic pixação Belo Horizonte built his own style. Moreover, we discuss the different times when graffiti mining beyond the limits of the landscape of the capital Belo Horizonte. We cover an area of more important socialities among pixadores, namely the festive graffiti. Later, handle times when pixadores gather around the launch of specialized DVDs that portray the practice of graffiti. Further, we explore the phenomenon of graffiti as cultural consumption, in order to discuss how pixadores produce their own products, so it will be clear to the reader how this production is complementary to the constitution of the person pixador. Finally, we discuss how the relations are ambiguous established by pixadores with the media, from a broader approach to the phenomenon, in order to investigate and question the given fact that graffiti is seen as a form of social deviance .